Pseudo-atrial flutter in a patient with heart-failure – Case report (Research, Society and Development, 2025)
This article aims to presente a case report of pseudo-atrial flutter in a 13-year-old-femal breed dog referred for examination after a positive test for dirofilariasis. The clinical examination and echocardiogram identified degenerative mitral valve disease stage ACVIM- B2. Serial ECG of the patient showed on the baseline, instead of true P waves, bursts of repetitive small deflections resembling sawtooth waves, with a frequency of 300/min (5 Hz), identified to as pseudo-atrial flutter. The P-QRS complexes were within normal reference range for the canine species.